Initiation and characterization of a glioblastoma multiforme derived cell line. (Colombia Medica, 2007)
Introduction: Cell lines and primary cultures are a useful tool for studying basic biology, development and therapy responses in cancer and nervous system tumors. Aim: To establish and characterize a human glioblastoma multiforme (GBM) derived cell line as an in vitro biological model to study nervous system cancer chemotherapy and gene therapy. Materials and methods: A resected tumor piece was obtained from a patient with clinical and histopathological diagnosis of GBM. It was processed to obtain viable cells to culture and histological sections, which were immunostained to glial fibrillary acid protein (GFAP) and S-100 protein (calcium binding protein) and to evaluate expression of apoptosis related proteins p53 and Bcl-2. Finally a cytogenetic evaluation was carried out. Results: Histopathological examination confirmed classic findings of GBM. Typical cytomorphological features of GBM were found in cells of the primary cultures: bipolar or unipolar cells, flat fibroblastoid cells, process-bearing cells with scant cytoplasm and 3 or more processes. It was found a differential expression of the four markers, which had a nuclear and cytoplasmatic staining pattern throughout studied subcultures. Cell line exhibited a high level of aneuploidy with modal chromosomal number between 43-45, with presence of poliploidy (55-102 < 4n>, XXYY) and endoreduplication (end 45, X, -Y). Conclusion: It was established a GBM derived cell line with a stable phenotype, maintaining morphological cell and cytogenetic characteristics.